Sex inequalities in HIV-related practices in the Brazilian population aged 15 to 64 years old, 2008 - Ana Roberta Pati Pascom; Célia Landmann Szwarcwald
The objective of this study is to analyze gender differences in HIV-related practices in the Brazilian population. A national survey was carried out in 2008 with a sample size of 8,000 individuals aged 15-64 years old. The sampling was stratified by macro geographical region and urban/rural areas. Logistic regression models were used to investigate the main predictors of consistent condom use. The results showed that women have less sexy, start sexual life later than men, have fewer casual sexual partners, but use condom less frequently than men. On the other hand, the coverage of HIV testing is significantly greater among women. Significant differences by gender were seen in all HIV-related risky practices. The greater vulnerability was always associated with women, with exception of HIV testing. The low proportion of condom use in infidelity situations was a problem for box sexes and deserves special consideration when developing prevention strategies.